The Policy Of The Death Penalty For Perpetrators Of Corruption Is Studied From A Sociological Perspective Of Law - Munasto, Daud (Fakultas Hukum Universitas Widya Mataram, 2022)
Corruption as an extraordinary crime provides regulations regarding the death penalty for the perpetrators. However, the fact is that this provision has never been applied by judges in adjudicating corruption cases. Therefore, corruption continues to occur and has expanded both the mode and the perpetrators. The formulation of Article 2 paragraph (2) UUTPK relating to